Non-crimp fabric composites : manufacturing, properties and applications - Lomov, Stepan V. (Woodhead Publishing in materials., 2011)
Non-crimp fabric (NCF) composites are reinforced with mats of straight (non-crimped) fibres, giving them such advantages as strength, ease of handling and low manufacturing costs. Non-crimp fabric composites provides a comprehensive review of the use of NCF composites, their manufacture and applications in engineering. Part one covers the manufacture of non-crimp fabrics, including also topics such as structural stitching and automated defect analysis. Part two goes on to discuss the manufacture of non-crimp fabric composites, with chapters covering such topics as deformability and permeability of NCF. Part three focuses on the properties of NCF composites, with chapters on stiffness and strength, damage progression and fatigue. Finally, part four covers the applications of NCF composites, including chapters on the aerospace and automotive industries as well as wind turbines and helicopter applications. The book concludes with a discussion of cost analysis of NCF composites in engineering applications. With its distinguished editor and international team of expert contributors, Non-crimp fabric composites is an essential reference for composite manufacturers and structural and mechanical engineers in industries using NCF composites, as well as academics with a research interest in the field. Provides a comprehensive review of the use of NCF composites, their manufacture and applications in engineeringReviews the manufacture of non-crimp fabrics, including also topics such as structural stitching and automated defect analysisExamines the properties of NCF composites considering stiffness and strength, damage progression and fatigue.